The Impacts of Oil and Gas Consumption on Life Expectancy - Mohd Shahidan, Shaari; Wan Sallha, Yusoff; Ahmad Nizam, Che Kasim; Miguel Angel, Esquivias; Faiz, Masnan; Muhammad Baqir, Abdullah (Regional Energy Resources Information Center (RERIC), Asian Institute of Technology, 2024)
This research aims to fill a notable need in current scholarly works by investigating the often-neglected impact of fossil fuel consumption, particularly oil and gas, on life expectancy. To examine the correlation between economic growth, national healthcare spending, and oil and gas usage on life expectancy in Malaysia from 1980 to 2020, we employ the Autoregressive Distributed Lag (ARDL) method, acknowledging its substantial implications for sustainable development. According to the findings of our study, the growth of the economy and the rise in the amount of gasoline consumed both have a positive impact on the average lifespan of individuals. In spite of this, the rise in the cost of medical treatment and the increase in the amount of oil that is consumed have a negative effect on life expectancy, both in the short term and in the long term. The coefficients have a substantial magnitude for a prolonged duration, highlighting the enduring influence. These results emphasize the need for policymakers to prioritize alternative energy sources and enhancements in healthcare quality to foster longevity and enhance the overall well-being in Malaysia. Furthermore, our study suggests that augmenting healthcare expenditure should be coupled with measures to ameliorate environmental quality for a more substantial positive impact on human well-being.